Biodegradation and Bioremediation - Alexander, Martin (Academic Press, 1999)
Alexander presents the basic principles of biodegradation and how these principles relate to bioremediation. All the subject's microbiological, chemical, toxicological, environmental, engineering and technological aspects are covered.